Perceived knowledge on type-2 diabetes of informal caregivers in rural communities of Thai Binh, Vietnam: Implications for health education - Thanh Duc Nguyen; Ib Christian Bygbjerg; Dan Wolf Meyrowitsch; Tine Gammeltoft; Cuong Duc Le; Ai Thi Nguyen; Jens Søndergaard (Elsevier, 2021)
Objectives: Informal caregivers' (ICGs') knowledge has substantial influence on the quality of caregiving. This study aims to identify caregivers' perceived knowledge status and analyse associations between their characteristics and perceived knowledge on how to care for individuals with type-2 diabetes (T2D). Study design: Cross-sectional study. Methods: Data were collected using a face-to-face survey with ICGs and perceived knowledge was evaluated on the 5-point Likert scale (ranging from 0 to 4). Results: Between April and July 2019, 1238 eligible ICGs were enrolled in the study. The mean age of participants was 48.3 years, about half (48.8%) were males and the majority (83.3%) were spouses or children of the person they cared for. ICGs mean knowledge score on overall activities was 2.48 (SD = 0.90); the highest score was seen for diet preparation (2.74 ± 0.85) and lowest for foot care (1.76 ± 1.45). Multivariate analyses showed that the following ICG characteristics were significantly more likely to result in a low level of T2D-related knowledge (mean score ≤2): age <40 years, educational level below high school, farming occupation, low economic status and caring for an individual with mild or moderate T2D. Conclusions: The level of perceived knowledge on T2D among ICGs was particularly low for the care of T2D complications. Development of targeted and tailored educational interventions for ICGs is recommended.